Konflik Batin dalam lagu “Berita Kepada Kawan“ Karya Ebiet G. Ade Kajian Psikologi - Veran Tika Agustin; Umi Kholidah; Rr Dwi Astuti (Jurnal Pendidikan Indonesia (JOUPI), 2023)
Conflicts that arise can cause problems both within oneself, between individuals and groups. These problems are very diverse, differences of opinion between a person's heart and mind can cause conflict. The conflict that arises can be in the form of inner conflict. This research aims to determine the inner conflict contained in the song Berita To Friends by Ebiet G. Ade using a literary psychology approach. By analyzing the lyrics of the song "Berita To Kawan" using a literary psychology approach, this research attempts to reveal the human emotions contained in the song lyrics and human psychology. The method used is qualitative descriptive. Based on data analysis that has been carried out on the lyrics of the song Berita Untuk Kawan by Ebiet G. Ade, it can be concluded that the forms of inner conflict that emerge are inner conflict of solitude, inner conflict of loneliness, inner conflict of suffering, inner conflict of sadness, inner conflict of tiredness, inner conflict of optimism and inner conflict of despair.